The pyrolysis behavior of evolved species from date palm seeds - Babiker, M.E. (EDP Sciences, 2014)
The pyrolytic behavior of evolved gases from date palm seeds (DPSs) were measured to gain insight into the mechanism of DPSs pyrolysis. Six different cultivars were used in this study, namely Deglet nour, Piarom, Suffry, Safawi, Mabroom and Aliya. A thermo-gravimetric analyzer (TGA) and a real-time gas analyzer (GA) were used to calculate the mass losses and the mole fraction of evolved gases, respectively. DPSs samples were pyrolyzed in an inert atmosphere condition using argon with a purge rate of 100 mL/minute. The samples were subjected to non-isothermal operation. An independent single model and parallel reaction model were adopted to interpret the empirical data collected from TGA and GA, respectively. The results reveled that there are three types of pyrolysis zones depending on the main constituents of every cultivars. Moreover, the potentialty of the zones in controlling the pyrolysis behavior was noticeable. The dominant hydrocarbon species in DPSs were CO and CH4 (40 to 50 higher than the rest of species). The mole fraction of CO was 2 to 4 times higher than the mole fraction of CO2. The activation energy and frequency factor of DPSs evolved species showed that Mabroom has the highest activation energy regarding H2 (63.21kJ/mol) and CO (74.32 kJ/mol). Â© 2014 Owned by the authors, published by EDP Sciences.